2016
DOI: 10.1016/j.micromeso.2015.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tungsten carbide on Al-SBA-15 mesoporous materials by carburization

Abstract: a b s t r a c t Aluminum was incorporated into SBA-15 supports at molar ratios Si/Al ¼ 10 and 2 by the pH-adjusting method. The calcined mesoporous Al-SBA-15 supports, as well as the Al-free SBA-15 support, were impregnated with ammonium paratungstate ((NH4)10[H2W12O42]4H2O) aqueous solution. Tungsten carbide (W2C) was synthesized by temperature programmed carburization (TPC) from the WO3 supported on Al-SBA-15 and SBA-15 in a flow of CH4/H2. These resultant materials were characterized by powder X-ray diffrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…3,5 Among the wide and different types of catalyst support, Santa Barbara Amorphous, commonly known as SBA-15, received great attention from the scientific community due to its properties, such as high surface area, high thermal stability, physical and chemical resistance. [6][7][8][9] These materials were successfully applied to several processes, including CO 2 capture, 10 adsorption of drugs from water, 11 removal of dyes from effluents, 12,13 and organic reactions, such as catalytic oxidation, 14 transesterification reactions for biodiesel production 15 and hydroxylation. 16 SBA-15 was first synthesized by Zhao et al in 1998 17 and rated as a mesoporous material according to IUPAC definition, 18 showing a pore diameter between 2-30 nm and a hexagonal twodimensional structure.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Among the wide and different types of catalyst support, Santa Barbara Amorphous, commonly known as SBA-15, received great attention from the scientific community due to its properties, such as high surface area, high thermal stability, physical and chemical resistance. [6][7][8][9] These materials were successfully applied to several processes, including CO 2 capture, 10 adsorption of drugs from water, 11 removal of dyes from effluents, 12,13 and organic reactions, such as catalytic oxidation, 14 transesterification reactions for biodiesel production 15 and hydroxylation. 16 SBA-15 was first synthesized by Zhao et al in 1998 17 and rated as a mesoporous material according to IUPAC definition, 18 showing a pore diameter between 2-30 nm and a hexagonal twodimensional structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, when comparing the materials obtained with Al insertion into the SBA-15 materials, observed is an increase in d (100) that is not dependent on the pH employed in the synthesis. Such behavior indicates that the Al inserted into the framework promotes larger values for the interplanar distance due to the length of the Si-O-Al bonds being longer than the Si-O-Si bonds [ 33 , 34 ]. In the materials synthesized with a pH of 2.0, the slight decrease in the d (100) value between the Si/Al molar ratios from 5 to 75 is possibly correlated with increasing the Al amount in octahedral coordination since the aluminum coordinated in tetrahedral form keeps constant for this pH.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that the diffractogram of the Pt-WO 3 /SBA-15 material (A) showed low-intensity peaks referring to the WO 3 species when compared to the material prepared by sequential impregnation (Pt-WO 3 /SBA-15 (B)). These low-intensity peaks can be attributed to a greater dispersion of WO 3 on the surface of SBA-15 incorporated by co-impregnation than by sequential impregnation, as discussed by ÁLVAREZ et al [46] studying the dispersion of WO 3 on the surface of the catalyst Al/SBA-15.…”
Section: X-ray Powder Diffraction (Xrd) Patternsmentioning
confidence: 89%
“…It is observed that samples prepared by co-impregnation were more sensitive to heat treatments than samples prepared by sequential impregnation. This behavior is attributed to an increase in the interaction of WO 3 particles with SBA-15 with a decrease in particle size and an increase in dispersion [46,47]. The co-impregnation method promoted an increase in the dispersion of WO 3 particles, favoring a better resistance to the thermal treatments of the materials.…”
Section: X-ray Powder Diffraction (Xrd) Patternsmentioning
confidence: 98%